2016
DOI: 10.1200/jco.2015.65.2560
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of the Acidic Beverage Cola on the Absorption of Erlotinib in Patients With Non–Small-Cell Lung Cancer

Abstract: Cola intake led to a clinically relevant and statistically significant increase in the bioavailability of erlotinib during esomeprazole treatment. In patients not treated with the PPI, the effects of cola were marginal. These findings can be used to optimize the management of drug-drug interactions between PPIs and erlotinib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 14 publications
0
78
0
2
Order By: Relevance
“…It was therefore investigated whether co‐administration of imatinib with an acidic beverage could increase the exposure to imatinib. This was previously described for erlotinib, but could not be substantiated for imatinib …”
Section: Methodsmentioning
confidence: 99%
“…It was therefore investigated whether co‐administration of imatinib with an acidic beverage could increase the exposure to imatinib. This was previously described for erlotinib, but could not be substantiated for imatinib …”
Section: Methodsmentioning
confidence: 99%
“…Erlotinib, a small molecule TKI used for non‐small cell lung cancer (NSCLC) and pancreatic cancer, also requires an acidic environment for absorption . Erlotinib concentrations were not found to be reduced in a study investigating erlotinib in combination with intravenous and oral pantoprazole; however, bioavailability was reduced when cola and esomeprazole were administered concomitantly with erlotinib . Furthermore, a study evaluating the effect of concomitant PPI or H2RA with erlotinib showed no significant effect on PFS or OS in patients with NSCLC .…”
Section: Introductionmentioning
confidence: 99%
“…It is just as important to seek out potential pharmacological strategies to eliminate this pharmacokinetic interaction. For instance, van Leeuwen and colleagues recently reported that simply ingesting the acidic beverage Cola with erlotinib improves its bioavailability in patients who are also receiving esomeprazole [31]. Moreover, this study highlights the importance of dietary factors – which are hard to control – in influencing the absorption of oncological TKIs.…”
Section: Discussionmentioning
confidence: 83%